CONTRASTIVE ANALYSIS OF FABRICS IN UZBEK AND ENGLISH LANGUAGES - Mamataliyeva Navbakhor Khujamberdiyeva; Boyqulova Fotima Zokirovna (Journal of new century innovations, 2024)
This article conducts a comprehensive exploration of fabric-related vocabulary in two distinct languages, Uzbek and English, employing a constructive analysis framework. This annotated exploration not only provides linguistic insights but also underscores the cultural, historical, and global dimensions that shape the fabric-related lexicon in Uzbek and English. The interplay of tradition and modernity is woven into the linguistic tapestry, reflecting the dynamic nature of language evolution in a globalized world.